Legalitas dan Akuntabilitas Keuangan Lembaga Filantropi dalam Keuangan Sosial Islam - Hasanah, Nuramalia; Ilham, Mochammad Fajar; Muhammad (Jurnal Ilmiah Wahana Akuntansi, 2023)
The practice of Islamic philanthropy that is rooted in the traditions of Indonesian society in the form of zakat, infaq, shadaqoh and waqf (ZISWAF) is growing, mainly due to the widening gap between rich and poor people and various natural disasters that come one after another. The role of the institution philanthropists Islam and the institution of amil zakat (LAZ) help many people who need help. The role of Islamic philanthropic institutions with the collection and allocation of zakat, infaq, sadaqah, and waqf (ZISWAF) funds provides benefits to the wider community in the economic development of the Ummah. This study aims to describe financial accountability for the management of funds of Islamic philanthropic institutions in the economic development of the Ummah. The data used in this study is secondary data obtained from the website of Indonesian philanthropic institutions. A total of 5 samples registered on the website of Indonesian religious philanthropic institutions. This study used quantitative methods using descriptive analysis. The results obtained were the Accountability of 5 philanthropic institutions that were sampled in the good category based on the results of indicators of accessibility and availability of financial statements. This research is useful for academics, philanthropic institutions and government